ANALISIS PENGARUH KUALITAS PELAYANAN, NILAI NASABAH, DAN KEPERCAYAAN TERHADAP WORD OF MOUTH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING PADA PT BANK BRISYARIAH KANTOR CABANG PEMBANTU UNGARAN - Aji, Yahya Pamungkas; Duriany, Embun (Jurnal Sains Ekonomi dan Perbankan Syariah, 2015)
AbstractThe research aim to analyze the influence significant variable of service quality, customer value, and trust toward word of mouth with customer satisfaction as intervening variable in PT Bank BRISharia Ungaran Branch Office. This research includes causality applied research. Data collection methods used were questionnaires, interviews, and literature. The population in this research are were all of savings customers in PT Bank BRISharia Ungaran Branch Office. The sampling technique used is judgemental sampling method. The samples in this research were 172 savings customers in PT Bank BRISharia Ungaran Branch Office. Data analysis model used Structural Equation Model (SEM) with analysis technique using t test that is operated by AMOS 22.0. The result in this research showed that service quality and trust influences positive and significant toward customer satisfaction, as well as customer satisfaction influences positive and significant toward word of mouth. While customer value influences positive and not significant toward customer satisfaction.Keywords:Service Quality, Customer Value, Trust, Customer Satisfaction, and Word of Mouth.